Impact of change in cropping pattern on bioenergy system design: Analysis and stochastic optimization. (September 2022) - Punnathanam, Varun; Shastri, Yogendra
Abstract: The availability of agricultural residues as feedstock for lignocellulosic biorefinery systems is uncertain due to changes in cropping pattern. This work first analyses the impact of change in cropping pattern on biorefinery systems considering both single and multi-feedstock systems. Subsequently, stochastic optimization is performed to generate a resilient design. For a case study of ethanol production in India, the deterministic single feedstock system was much less economical than the multi-feedstock system, with an associated ethanol cost of ₹89/l ($1.2/l) and ₹56/l ($0.76/l), respectively. The resilient design for the multi-feedstock system resulted in an ethanol cost of ₹55/l ($0.75/l) and showed up to 60% lesser variation as compared to the deterministic design. Changes in cropping pattern were shown to primarily impact the feedstock procurement and transportation expenses. The results imply that the expected cropping pattern changes must be taken into account while designing biorefinery systems. Highlights: Optimal design of lignocellulosic biorefinery system considering uncertain land use. Stochastic optimization model developed and solved to generate resilient design. Comparison of single and multi-feedstock systems. Implementation on real world case study of Maharashtra, India. Resilient design shown to have drastically lower sensitivity to land use change.